Cystadenoma in a pediatric patient: a rare salivary gland neoplasm - Glória Maria França; Weslay R. Silva; Cristianne K. Medeiros; Joaquim Felipe Junior; Adriano R. Germano; Hébel C. Galvão
ABSTRACT Salivary gland cystadenoma is a rare benign neoplasm, representing 1.4% of all benign salivary gland tumors. It presents a predilection for the major salivary gland and middle-aged or elderly adults. The present study reports a rare case of cystadenoma in the floor of the mouth a 5-year-old male patient, who was referred to an oral diagnosis center for evaluation of the lesion. After performing an incisional biopsy, microscopic analysis revealed a cystadenoma. The patient's treatment was excision of the lesion and he has been under follow-up for one year with no signs of recurrence.